Effects of professional skepticism, ethical environment, moral intensity and independence threat on auditors’ ethical decision making / Yanto Kamarudin - Kamarudin, Yanto (2022)
A distinguishing mark of the audit profession is its responsibility to act in the public interest rather than exclusively to satisfy the needs of an individual client. In this position, auditors are expected to protect the interest of wider stakeholder rather than their individual clients or their own. The need to satisfy multiple stakeholders creates conflicts for the auditors and most of the time, it is difficult to reconcile and satisfy the different needs and interests of all stakeholders and may require auditors to perform unethical behavior. The unethical behavior of auditors can be evidenced by the recent financial scandals such as Carillion, Patisserie Valerie, General Electric, BHS, and Wirecard. These financial scandals and other continuous financial scandals have made regulators, researchers and other stakeholders to focus on auditors’ ethical behaviour, auditor independence and professional skepticism. Thus, this study focusses on the relationship among professional skepticism, ethical environment, moral intensity, and independence threat towards auditors’ ethical decision making. Ethical behavior of auditors can be evidenced in all stages of audit process. As such, this research focuses on the auditors’ ethical decision making in both the execution stage (Study One) and the completion stage (Study Two) of audit process. The two studies are required to provide a better understand of auditors’ ethical decision making when they are facing with ethical dilemma since auditors need to make ethical decision in all stages of audit process in particular in execution and reporting stage. 183 auditors participated in the Study One and 121 auditors participated in the Study Two from the ten largest audit firm in Indonesia. The data is analyzed using the partial least squares structural equation model (PLS-SEM). The study results in several findings. In Study One, trait professional skepticism may affect the auditors’ ethical decision making only under the quality threatening scenario but not under-reporting scenario. In addition, Study One finds that ethical environment may affect the auditors’ ethical decision making only under the quality threatening scenario but not under-reporting scenario. Study One also notes that the level of moral intensity is higher for quality threatening behavior than under-reporting time scenario. On contrary, Study Two finds that state professional skepticism does not affect auditors’ ethical decision making. Study Two also finds that ethical environment does not have any effect on auditors’ ethical decision making. However, Study Two finds that moral intensity has effects on auditors’ ethical decision making. Despite the criticism that auditors tend to pursue their commercial interest, Study Two finds that despite auditors do not consider independent threat as an ethical issue, but they can still act ethically. The higher the independence threat faced by an auditor, the higher the ethical behavior of such auditor. Thus, audit profession still can play an important role to secure public trust. Further, the study also finds that there are sequential relationships among ethical components proposed by Rest (1986). Study Two also find that moral intensity mediates the relationship between state professional skepticism and ethical judgment, ethical intention, and ethical behavior. Further, ethical environment moderates the relationship between moral intensity and auditors’ ethical behavior. However, independence threat does not moderate the relationship between moral intensity and auditors’ ethical behavior. The findings from this study suggest the need for ethical environment of audit firm to ensure the auditors can act ethically during the audit process. In addition, the need for ethics and independence training is required to enhance auditors’ ethical decision making.